Design of α‐Selective Glycopyranosyl Donors Relying on Remote Anchimeric Assistance. Issue 1 (20th January 2016) - Komarova, Bozhena S.; Tsvetkov, Yury E.; Nifantiev, Nikolay E.
Abstract: Oligosaccharides have a variety of versatile biological effects, but unlike peptides and oligonucleotides, investigation of the roles of oligosaccharides is not easy. Since biosynthesis of oligosaccharides does not comply with direct genetic control, their isolation from natural sources and biotechnological preparation are complicated, due to the heterogeneous composition of raw carbohydrates. Oligosaccharide synthesis is needed for the establishment or confirmation of the structure of natural glycocompounds. Also, synthetically prepared, defined oligosaccharides and their derivatives are becoming increasingly important tools for many biological and immunological research projects. The key step of oligosaccharide synthesis involves glycosylation, a reaction that builds glycosidic bonds. Usually, construction of 1, 2‐ trans ‐bonds is easy, and therefore, this reaction can even be included into automated syntheses. At this time, installation of the 1, 2‐ cis ‐bond remains simultaneously frustrating and compelling. In our and other laboratories, a strategy of α‐selective (1, 2‐ cis ) glycosylation, relying on remote anchimeric assistance with acyl groups, is studied. The state of the art in this work is summarized in this review. Abstract : Design of α‐Selective Glycopyranosyl Donors Relying on Remote Anchimeric Assistance : Glycopyranosyl donors bearing remote participating acyl groups are advantageous tools for stereoselective 1, 2‐ cis ‐glycosylation.